The use of frequency ratios to diagnose structural damage in varying environmental conditions. (February 2020) - Surace, C.; Bovsunovsky, A.
Highlights: The theory for obtaining natural frequencies and mode shapes of a damaged multi-span beam is shown. The model of crack-like damage in the hollow concrete beam is developed. Frequencies ratios are proposed as damage characteristics in varying environmental conditions. Analytical results are presented for a multi-span beam-like structure simulating a bridge. Experimental results are presented for two real structures: the Z24 bridge - the Sanctuary of Vicoforte. Abstract: One of the main problems of damage vibration diagnostics based on the change of natural frequencies of structures is the influence of ambient and operational factors (temperature, humidity, wind, heavy traffic etc.) on natural frequencies. In some cases, this effect is comparable or even more significant than the effect of damage itself and reliable diagnostics of damage becomes problematic. In this paper, the use of the ratios between natural frequencies of different mode shapes is proposed as a characteristic of damage rather than the change of natural frequencies. The study has demonstrated that these ratios are fundamentally unaffected by the environmental and operational factors. Application of the proposed method is illustrated using the examples of the Z24 prestressed concrete bridge and the Sanctuary of Vicoforte. Firstly, an analytical study was performed to calculate the mode shapes and natural frequencies of damaged multi-span beam-like structure taking into account the model of crack-like damage in a hollow concrete beam. The results reveal that, in order to identify local damage of subcritical size, natural frequency data of at least four modes of vibration are necessary. Secondly, the natural frequencies acquired experimentally on the Z24 bridge and Sanctuary of Vicoforte have been used to prove that the ratios between natural frequencies can be a useful diagnostic tool in the field of structural health monitoring.